Inflammation Prevention Program: as an Effort to Prevent Mastitis in Breastfeeding Mothers in the White Lotus Posyandu I Pungkuran Pleret Bantul - Riza Yulina Amry; Anna Nur Hikmawati; Bety Agustina Rahayu (Jurnal Peduli Masyarakat, 2020)
Breastfeeding is one of the gifts of a woman who can give milk directly to her child. Breast milk is the best food for babies that supports the growth and development of babies. Breast milk contains many substances that are not found in any food and drink, including the most expensive and best formula milk. The number of exclusive breastfeeding coverage in Indonesia is still far from the target. Mastitis is one of the causes of the lack of exclusive breastfeeding. Lack of mother's knowledge about breast care and breastfeeding can cause errors in breastfeeding position which results in mastitis. Community service is carried out as an effort to prevent inflammation / mastitis in nursing mothers in the White Lotus Posyandu I region of Pungkuran Pleret Bantul. Community service activities were attended by 26 mothers of children under five. The method used for the delivery of material is health education and demonstrations. The questionnaire was used as an instrument to measure participants' knowledge before and after the activity. The material is delivered using audiovisual media, which is presented in powerpoints and leaflets. Subthemes of material presented in this activity include inflammation, mastitis, breast care, and how to breastfeed properly. Measurement of the results of the pretest and posttest knowledge of the mother with the help of Microsoft Excel. PKM results show an increase in maternal knowledge, pretest results show 54% of mothers with sufficient knowledge and 46% of mothers with good knowledge. Posttest results showed 100% results with good knowledge. Conclusions from the results of the PKM inflammation prevention program: as an effort to prevent mastitis in breastfeeding mothers, the Posyandu Putih Teratai I Region of Pungkuran Pleret Bantul has a positive impact on increasing maternal knowledge.